(untitled) (Castilla. Estudios de Literatura, 2017)
This paper examines the narrative resources and literal treatments of two Chinese characters in two short-stories from the illustrated magazine La Ilustración Española y Americana, the first of which, published at the end of 19th century and, the second, at the beginning of 20th century. The purpose of this study is to demonstrate an evolution of the Chinese stereotype in Spanish literature in the context of the so-called fin de siècle.